Development of a job stressor scale for nurses caring for patients with intractable neurological diseases - Ando, Yukako; Kataoka, Tsuyoshi; Okamura, Hitoshi; Tanaka, Katsutoshi; Kobayashi, Toshio (Hiroshima journal of medical sciences, 2013)
The purpose of this research is to verify the reliability and validity of a job stressor scale for nurses caring for patients with intractable neurological diseases. A mail survey was conducted using a self-report questionnaire. The subjects were 263 nurses and assistant nurses working in wards specializing in intractable neurological diseases. The response rate was 71.9% (valid response rate, 66.2%). With regard to reliability, internal consistency and stability were assessed. Internal consistency was examined via Cronbach's alpha. For stability, the test-retest method was performed and stability was examined via intraclass correlation coefficients. With regard to validity, factor validity, criterion-related validity, and content validity were assessed. Exploratory factor analysis was used for factor validity. For criterion-related validity, an existing scale was used as an external criterion; concurrent validity was examined via Spearman's rank correlation coefficients. As a result of analysis, there were 26 items in the scale created with an eight factor structure. Cronbach's a for the 26 items was 0.90; with the exception of two factors, alpha for all of the individual sub-factors was high at 0.7 or higher. The intraclass correlation coefficient for the 26 items was 0.89 (p < 0.001). With regard to criterion-related validity, concurrent validity was confirmed and the correlation coefficient with an external criterion was 0.73 (p < 0.001). For content validity, subjects who responded that "The questionnaire represents a stressor well or to a degree" accounted for 81% of the total responses. Reliability and validity were confirmed, so the scale created in the current research is a usable scale.